2010
DOI: 10.1007/s11046-010-9276-7
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis Caused By Sporothrix globosa in Rio De Janeiro, Brazil: Case Report

Abstract: This report describes the first isolation of Sporothrix globosa from a Brazilian patient. A 77-year-old woman was examined for sporotrichosis infection. Histopathological examination of skin biopsy revealed chronic granulomatous infiltrate with microabcess. Furthermore, S. schenckii-like yeasts were evident as demonstrated by PAS and Grocott stains. The fungus was identified based on colony morphology on Sabouraud Dextrose Agar slants, Potato Dextrose Agar, and Corn Meal Agar, microscopic morphology on slides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 22 publications
1
59
0
1
Order By: Relevance
“…By associating phenotypic and genotypic features, Marimon et al (13) recognized three new species, Sporothrix brasiliensis, Sporothrix globosa, and Sporothrix mexicana, and proposed an identification key for these Sporothrix species. S. globosa has worldwide distribution (12,18), whereas S. brasiliensis is apparently restricted to Brazil (13) and S. mexicana to Mexican environmental samples (13), although the latter was recently identified in Portugal (3). Additionally, these authors have proposed the promotion of S. schenckii var.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By associating phenotypic and genotypic features, Marimon et al (13) recognized three new species, Sporothrix brasiliensis, Sporothrix globosa, and Sporothrix mexicana, and proposed an identification key for these Sporothrix species. S. globosa has worldwide distribution (12,18), whereas S. brasiliensis is apparently restricted to Brazil (13) and S. mexicana to Mexican environmental samples (13), although the latter was recently identified in Portugal (3). Additionally, these authors have proposed the promotion of S. schenckii var.…”
mentioning
confidence: 99%
“…The genotypic analyses also allowed the correction of phenotypic misidentifications, such as for the isolate IPEC27722, which was phenotypically characterized as S. mexicana but grouped within the S. schenckii cluster, as well as for the isolates IPEC27133, IPEC27100, and IPEC28329, which identified as S. schenckii but clustered with S. brasiliensis. Identification of the Sporothrix species complex has been based on a polyphasic approach using a combination of phenotypic methodologies and sequencing (13,14,18,19). The proposed identification key based on phenotypic tests (13) was reported as easy and reliable for species differentiation without the need of molecular techniques.…”
mentioning
confidence: 99%
“…In addition, Marimon and collaborators (2007) supported these findings by suggesting that, according to a combination of phenotypic and genetic features, S. schenckii should not be considered a single taxon that causes sporotrichosis in human and animals but should instead be considered a species complex that is comprised of at least four species: S. brasiliensis, S. globosa, S. luriei, and S. schenckii (Marimon et al, 2006(Marimon et al, , 2007(Marimon et al, , 2008. S. globosa is distributed worldwide (Madrid et al, 2009;Oliveira et al, 2010), whereas S. mexicana is restricted to Mexico and S. brasiliensis to Brazil. Also, S. brasiliensis, S. globosa and S. luriei are related as etiological agents of sporotrichosis (Marimon et al, 2007(Marimon et al, , 2008.…”
Section: Molecular or Dna-basedmentioning
confidence: 99%
“…To the Editor: Sporotrichosis is a subcutaneous fungal infection present worldwide that is caused by traumatic inoculation or inhalation of spores of the dimorphic fungus Sporothrix schenckii complex (1)(2)(3). However, molecular studies have shown that the S. schenckii complex constitutes several cryptic infectious species (i.e., S. albicans, S. brasiliensis, S. globosa, S. luriei, S. mexicana, and S. schenckii).…”
mentioning
confidence: 99%
“…The species showed distinct pathologic behavior, antifungal responses, and phenotypes, which suggests that optimal clinical treatment may depend on the taxon involved in the sporotrichosis (1). Human infections have been reported primarily from the Americas, including Latin America (3,5). Asia (e.g., Malaysia, India, Japan), Africa, and Australia are also regions where infections are endemic (6).…”
mentioning
confidence: 99%